IMPLEMENTASI MODEL DISCOVERY LEARNING BERBASIS SHARED READING UNTUK PENINGKATAN KEMAMPUAN MEMBACA TEKS SEDERHANA SISWA KELAS RENDAH - Ulfa Dwi Nur Afifah; Panca Dewi Purwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the implementation and analyze the effectiveness of Discovery Learning integrated with Shared Reading in improving early reading skills of first-grade students at SDN 02 Nongkosawit Semarang. A mixed-method approach with an explanatory sequential design was used involving 20 students. Data were collected through observations, reading tests, questionnaires, and documentation. The findings reveal improved reading performance, with the average score increasing from 62 to 82 and 90% of students achieving mastery (≥70). Students also showed higher participation, confidence, and better understanding of simple texts. Therefore, the Discovery Learning-based Shared Reading model is proven effective for strengthening early literacy in lower-grade elementary students.